Dietary Micronutrients and Gender, Body Mass Index and Viral Suppression Among HIV-Infected Patients in Kampala, Uganda - Nathan Isabirye, MPHN; Amara E. Ezeamama, PhD; Rachel Kyeyune-Bakyayita, MBChB, PhD; Danstan Bagenda, PhD; Wafaie W. Fawzi, MBBS, DrPH; David Guwatudde, PhD (Global Health and Education Projects, Inc., 2020)
Background: HIV/AIDS is a hallmark of immune suppression. Micronutrient deficiencies in diet and recurrent opportunistic infections play major roles in the lives of people living with HIV. Although benefits of providing adequate diet to HIV positive persons are well documented, the demand for key elements still remain unclear in particular settings, especially in low and middle-income countries. Methods: This was a cross sectional analysis of baseline data collected from HIV-infected adults initiating antiretroviral therapy, and who were enrolled in a multivitamin supplementation trial. A food frequency questionnaire was used and intake were obtained as a product of quantities consumed. Adequacy was calculated as the proportion of Recommended Dietary Allowances (RDA). A chi square test and logistic regression analysis were used at p-value 0.05 to show significant associations. Results: Mean intakes were above minimum requirements for analyzed micronutrients with the exception of Calcium and Iron. Participants who met RDA intakes were as follows: highest (? 80%) for Magnesium, Selenium, Zinc and Vitamins B2, B6, B9, C and E; moderate (50% to <80%) for Vitamins B3, and A; and lowest (?50%) for Iron (30%), Calcium (14.9%), Vitamins B12 and B1. Gender differences in met RDA were observed for Iron, Selenium, Zinc, Vitamins A, B1, B3 and E. In multivariable analyses, nutritional status and CD4 count had no influence on meeting RDA for majority of micronutrients such as magnesium, Selenium, B class vitamins (B1, B2, B3, B6, B9, B12), vitamin (A, C, and E), Zinc and Calcium, but not including iron. Conclusion and Global Health Implications: Diets consumed by the study participants were low in most protective nutrients (Iron, Calcium, Zinc, Vitamin A, B1, B3, and B12). This deficiency was more common among females than males, and irrespective of BMI or CD 4 count. Findings warrant further investigation on the impact and cost implications for suplementation interventions that target the elements lacking in the diets of people living with HIV in similar low-resourced settings. Key words: • Recommended Dietary Allowances • Micronutrients • Dietary intakes • Body Mass Index • CD4 cell count • HIV/AIDS • Uganda   Copyright © 2020 Isabirye et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0) which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in this journal, is properly cited.